(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The article provides information about the morphology and function of the kidneys in children with obesity. The influence and interrelationship of numerous pathogenetic factors affecting the functioning of the kidney is discussed. The peculiarity of obesity nephropathy in children compared with the adult body was noted.